2005
DOI: 10.1302/0301-620x.87b8.16011
|View full text |Cite
|
Sign up to set email alerts
|

Results of a hydroxyapatite-coated (Furlong) total hip replacement

Abstract: We describe the survival of 134 consecutive JRI Furlong hydroxyapatite-coated uncemented total hip replacements. The mean follow-up was for 14.2 years (13 to 15). Patients were assessed clinically, using the Merle d'Aubigné and Postel score. Radiographs were evaluated using Gruen zones for the stem and DeLee and Charnley zones for the cup. Signs of subsidence, radiolucent lines, endosteal bone formation (spot welds) and pedestal formation were used to assess fixation and stability of the stem according to Engh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 27 publications
5
44
1
Order By: Relevance
“…Calcar atrophy was also noted in other follow-up studies for the Furlong HAC stem, indicating resorption in Gruen zone 7. 42,43 Moreover, Singh et al 43 noted formation of new bone extending from the femoral cortex to the stem-tip, i.e. in Gruen zone 4, consistent with the slight increase in strain at GZ-4 observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…Calcar atrophy was also noted in other follow-up studies for the Furlong HAC stem, indicating resorption in Gruen zone 7. 42,43 Moreover, Singh et al 43 noted formation of new bone extending from the femoral cortex to the stem-tip, i.e. in Gruen zone 4, consistent with the slight increase in strain at GZ-4 observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The relatively young mean age of the cohort relates to the senior author's preference to use cementless hips in young patients in an attempt to preserve bone stock for subsequent revision surgery and is comparable to the mean ages from similar studies using the ABG I prosthesis [2,8,12]. A metal-onpolyethylene bearing (sterilized through gamma irradiation [25][26][27][28][29][30][31][32][33][34][35] in air) with a stainless steel 28-mm-diameter head was used in all hips.…”
Section: Methodsmentioning
confidence: 89%
“…In comparison, our study showed a different pattern of bone remodeling with greater preservation of bone density in the distal medial and the distal lateral cortex with the uncemented stem. Longitudinal noncomparison studies with Charnley cemented prostheses [5] have observed that at 1 year, there was a reduction in BMD of 6.7% in the calcar region and an increase of 5.3% in the femoral shaft distal to the tip of the implant [22]. Studies with an uncemented HA-coated prosthesis [19] showed that the BMD was lower in Gruen Zones 1 and 7 and concluded prosthesis design influences periprosthetic bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…With good survival of the HA-coated Furlong 1 cup and stem [22], better preservation of periprosthetic bone would potentially make revision surgery less complex and also possibly decrease the risk of periprosthetic fracture. Additional long-term studies of remodeling and periprosthetic bone density between cemented and uncemented implants can help us understand preservation and behavior of periprosthetic bone stock.…”
Section: Discussionmentioning
confidence: 99%